2022
DOI: 10.1038/s41598-022-16398-7
|View full text |Cite
|
Sign up to set email alerts
|

Innovative targets of the lncRNA-miR-mRNA network in response to low-dose aspirin in breast cancer patients

Abstract: This study aimed to investigate innovative targets in breast cancer patients by considering the interaction of the lncRNA-miR-mRNA network in response to low-dose aspirin. The candidate miRs were first taken from the GEO and TCGA databases. Then, the candidate network was constructed using the high-throughput sequencing data. The expression levels of candidate targets were finally measured using Real-Time PCR in luminal A breast cancer patients undergoing aspirin (80 mg daily for three months) and non-aspirin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Depending on their functions and pattern of expression, they can be divided into tumor suppressors and oncogene classes 11 . In addition, growing exploratory evidence supports the idea that LncRNAs function as competitive endogenous RNAs (ceRNAs), which compete for microRNA (miRNA) binding to their upregulated target genes 12 . The ceRNA theory can critically help to understand and identify the function of lncRNA 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Depending on their functions and pattern of expression, they can be divided into tumor suppressors and oncogene classes 11 . In addition, growing exploratory evidence supports the idea that LncRNAs function as competitive endogenous RNAs (ceRNAs), which compete for microRNA (miRNA) binding to their upregulated target genes 12 . The ceRNA theory can critically help to understand and identify the function of lncRNA 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral blood cells of invasive BC patients produced high levels of IL-1β, leading to metastasis [ 69 ]. In sera and plasma of BC patients, ELISA findings showed that IL-β expressions were significantly increased compared to those in the control group [ 70 , 71 ]. Remarkably, IL-1β is secreted via not only the inflammasome pathway [ 143 ], but also NF-κB [ 115 , 116 ] which is activated via extracellular ATP [ 147 ] and the purinergic receptor P2X7R [ 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with invasive BC, IL-1β production by peripheral blood cells was associated with lymphatic metastasis [ 69 ]. Enzyme-linked immunosorbent assay (ELISA) findings showed that IL-β expressions were significantly increased in the sera and plasma of BC patients compared to the control group [ 70 , 71 ] and were related to tumor size, clinical stage, histological grade, and lymph node metastasis [ 70 ]. In addition, patients with metastatic BC exhibited an increased production of IL-1β compared to patients with early BC [ 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…The qRT-PCR reactions were performed with an ABI StepOne Plus System (Applied Biosystems; Thermo Fisher Scientific, Inc.). The expression level of the genes was calculated according to the 2−ΔΔCT method 54 .…”
Section: Methodsmentioning
confidence: 99%